The significance of adiponectin as a biomarker in metabolic syndrome and/or coronary artery disease - Stojanović, Sanja S; Deljanin Ilić, Marina; Ilić, Stevan; Petrović, Dejan; Djukić, Svetlana (Vojnosanitetski pregled, 2015)
Background/Aim. Adiponectin exerts profound protective actions during insulin resistence or prediabetes progression towards more severe clinical entities such as metabolic syndrome and/or cardiovascular disease. Since hypoadiponectinaemia contributes to the pathophysiology of the metabolic syndrome and coronary artery disease the level of circulating adiponectin may be an early marker of cardiovascular events. The aim of this study was to determine the relationships between serum adiponectin levels and parameters of both insulin sensitivity and obesity in patients with the metabolic syndrome and/or coronary artery disease, as well as to assess predictive value of adiponectin serum levels as a biomarker of these entitetis. Methods. The study included 100 patients with metabolic syndrome and/or coronary artery disease with different degree of insulin resistance and healthy, normoglycemic individuals. The control group comprising healthy, normoglycemic individuals was used for comparison. Serum level of adiponectin, fasting glucose, fasting insulinemia Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) index and anthropometric parameters were determined in all the subjects. Adiponectin was measured by using the ultrasensitive ELISA method. Insulinemia was measured by the radioimmunoassay (RIA) method. The presence of glycemic disorders was assessed on the basis of oral glucose tolerance test (OGTT). Results. Adiponectin level was inversely correlated with age (ρ = - 0.015), parameters of both obesity (R = 0.437; p < 0.001) and insulin resistance (R = 0.374; p < 0.01). Decreasing in the level of adiponectin was strongly implicated in the development of insulin resistance. Most importantly, a statistically significant rapid decrease in adiponectin was in the prediabetic stages (p < 0.01).  The predictor value of adiponectin was 1,356.32 ± 402.65 рg/mL. Conclusions. The obtained resultats suggest that adiponectin may be a useful marker in identification of individuals with risk of developing metabolic syndrome and coronary artery disease, as well as a predictor of prediabetes.
Keywords: adiponectin; biological markers; metabolic syndrome x; coronary disease